Frequency of Preterm Labour in Women Presenting with Short Interpregnancy Interval - Rukhsana, Farzana Khan, Summiya Ramzan, Rehana Kamal, Roona Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Short interpregnancy intervals have an adverse effect on maternal and neonatal outcome. The aim of this study is to determine the frequency of preterm labour in women presenting with short interpregnancy interval. Aim: To determine the frequency of preterm labour in women presenting with short interpregnancy interval. Study design: Cross-sectional study. Place and duration of study: Department of Obstetrics & Gynaecology Unit 2, Sandeman Hospital, Quetta from 8th December 2018 to 8th June 2019. Methodology: One hundred and ninety three patients were enrolled. After taking informed written consent history and clinical examination was done and all the follow-ups were monitored till the complete 37 weeks of gestation or the outcome i.e. preterm labour. Result: The mean age of mothers was 27.057±3.942 years. The mean interpregnancy interval was 14.880±2.084 months. The preterm labour was noted in 32 women (16.6%). Conclusion: Short interpregnancy interval was commonly observed in preterm labour. Awareness programs and family planning would prove advantageous in minimizing its associated risk both for mother and the newborn.